Immuno-histochemical features of the structure of foetuses’ ovarian from the mothers with pregnancy complications - Kupriianova, Larisa (Journal of Education, Health and Sport, 2017)
Kupriianova Larisa. Immuno-histochemical features of the structure of foetuses’ ovarian from the mothers with pregnancy complications. Journal of Education, Health and Sport. 2016;6(11):749-759. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.275714 http://ojs.ukw.edu.pl/index.php/johs/article/view/4244 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. UDK: 618.11-053.18-091.8:618.3-06 Immuno-histochemical features of the structure of foetuses’ ovarian from the mothers with pregnancy complications Larisa Kupriianova Kharkiv National Medical University, Kharkov, Ukraine Abstract As a material of our research, we took into account foetuses’ ovarian at the gestation term from 21 to 42 weeks; and, as a result, all types of material we divided into few groups: foetuses from healthy mothers; foetuses from mothers with pre-eclampsia complications of pregnancy of different stages; foetuses from mothers with pregnancy’s complications as a chronical infection. Research methods: organomethrical, histochemical, immuno-histochemical, statistical. As a result of the complex research, in foetuses’ ovarian from mothers with pregnancy complications of different types, we can see reducing of indicators of structural and functional activity of organs, increasing of apoptotic index; increasing of endothelin-1 production; decreasing of hormones production. Key words: fetus, pregnancy, pre-eclampsia; infection, ovary.